Prevalence and Risk Factors of Umbilical Port-Site Infections Following Cholecystectomy - Anwar Sayed, Muslihuddin, Nasir Iqbal, Nisar Ahmad Khan, Saifurrahman, Ammara Rafi Orakzai (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: One of the most frequent side effects after laparoscopic cholecystectomy is umbilical port-site infections, leading to increased morbidity and prolonged recovery. Identifying the prevalence and associated risk factors is essential for implementing preventive strategies to improve patient outcomes. Methodology: This cross-sectional study was conducted at the Department of Surgery, Saidu Teaching Hospital, Swat, from October 2022 to March 2023. The study comprised 93 individuals who had laparoscopic cholecystectomy. Demographic data, comorbidities, operative factors, and postoperative outcomes were recorded. Umbilical port-site infections (UPSI) were diagnosed based on clinical signs and confirmed via microbiological analysis. At a significance level of p < 0.05, statistical analysis was conducted using the logistic regression analysis, independent t-test, and chi-square test. Results: The prevalence of UPSI was 14.0% (n = 13). Obesity (p = 0.021), diabetes mellitus (p = 0.007), and smoking (p = 0.012) were significant risk factors. Intraoperative factors such as prolonged operative time (p = 0.003), bile spillage (p = 0.018), and simple suturing of the port site (p = 0.026) were also significantly associated with infection. Staphylococcus aureus (38.5%), Escherichia coli (30.8%), and Pseudomonas aeruginosa (23.1%) were the most frequently isolated pathogens. Conclusion: UPSIs remain a notable concern following laparoscopic cholecystectomy, with obesity, diabetes, smoking, prolonged surgical duration, and bile spillage contributing to increased risk. Preventive measures, including meticulous surgical techniques, optimal wound closure, and targeted antimicrobial prophylaxis, are essential to reducing infection rates. To enhance surgical results and optimize these procedures, more extensive research is required. Keywords: Umbilical port-site infection, laparoscopic cholecystectomy, risk factors, surgical site infection, microbiological analysis, bile spillage.